Factors that Predict Neutropenia in Korean Patients with Advanced Urothelial Cancer after Cisplatin- Based Systemic Chemotherapy - Kwon, Whi-An; Oh, Tae Hoon; Lee, Jea Whan; Seo, Ill Young; Park, Seung Chol (Urology Journal, 2018)
Purpose: The aim of this study was to identify factors that can be used to predict severe neutropenia (grade 3 or higher) in patients with advanced urothelial cancer after cisplatin-based systemic chemotherapy. Materials and Methods: The study examined 79 Korean patients with advanced urothelial cancer who were treated with several cycles of cisplatin-based systemic chemotherapy from May 2006 to May 2015. Risk factors for neutropenia (grade 3 or higher) and for the occurrence of neutropenia (grade 3 or higher) during the first cycle of chemotherapy were examined. Result: Thirty-six out of the 79 patients (45.6%) developed neutropenia at grade 3 or higher during the first cycle of cisplatin-based systemic chemotherapy: 18 (22.7%) of these experienced grade 3 neutropenia and 18 (22.7%) experienced grade 4. Multivariate analysis identified pretreatment neutrophil counts (P = .001) as the only significant factor predictive for severe neutropenia. Conclusion: The pretreatment neutrophil count was found to be the factor that poses a significant and independent risk in development of severe neutropenia induced by applying cisplatin-based systemic chemotherapy to patients with advanced urothelial cancer.